(untitled) (Agronomy Journal of Nepal, 2021)
Weeds have been a major constraint in maize cultivation resulting in huge economic loss to farmers. A field experiment was conducted at Dhading Besi, Nepal to evaluate the effect of different weed management practices on weed dynamics, yield and economics of spring maize in 2020. The experiment was laid out in Randomized Complete Block Design (RCBD) comprising of eight treatments with three replications. Rajkumar hybrid maize variety was used in the experiment. The treatments consisted of weedy check, weed free, atrazine as PE @1.0 kg a.i./ha, pendimethalin as PE @1.0 kg a.i./ha, atrazine @ 1.0 kg a.i./ha as PE followed by (fb) 2,4-D EE @0.5 kg a.i./ha as PoE, pendimethalin @ 1.0 kg a.i./ha as PE fb 2,4-D EE @ 0.5 kg a.i./ha as PoE, 2 hand weeding @ 20 and 40 DAS and Farmer’s practice. The experiment result revealed that sequential application of atrazine fb 2,4-D EE treatment resulted in highest grain yield (11.37 t/ha) which was statistically similar with weed free (11.24 t/ha) and followed by the treatment atrazine (10.36 t/ha). 16 weed species belonging to 6 different families were identified. The broad leaf weeds and grassy weeds were more prominent than sedges. The total density and dry weight of weeds were found significantly lower in sequential application of atrazine fb 2,4-D EE than other treatments. Similarly, application of atrazine fb 2,4-D EE resulted in maximum weed control efficiency of 87.59 %, 95.91 % and 92.17% at 30, 45 and 60 DAS respectively. The lowest weed index (-1.27%) was also obtained in the application of atrazine fb 2,4-D EE. Yield loss due to weed in the weedy check treatment was found to be 50.99% followed by farmer’s practice (43.17%). The benefit cost ratio and increment in benefit over weedy check were highest in atrazine fb 2,4-D EE followed by atrazine and significantly better than other weed management treatments. The sequential application of atrazine fb 2,4- D EE was found to be the most effective in controlling weeds, high yielding and economical among the different weed control treatments. The application of atrazine one time as PE was found to be next better option for weed control in spring maize.